PENGARUHGAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASARDENGAN MOTIVASIDAN INOVASI GURU SEBAGAI VARIABEL INTERVENING DIEKS KOTA ADMINISTRATIF JEMBER - Mahardika Wardhana Monoyasa; Raden Andi Sularso; Dewi Prihatini (RELASI : JURNAL EKONOMI, 2017)
This research is an explanatory research conducted at elementary school in Ex City Administrative of Jember. This research method uses structural equation modeling. There are 16 primary schools that serve as research sites with a population of 128 teachers. The sample in this research is 116 people. This research uses two stage sampling, where nonprobability sampling method that is purposive sampling is applied to determine research place and second stage when determining research sample.The results of this study indicate that the headmaster's transformational leadership style positively and significantly influence teacher performance with path coefficient 0,147, probability equal to 0,012, and CR value 2,892. The results of the study showed a positive and significant outcomes between the principal transformational leadership style to teacher motivation and teacher motivation to teacher innovation. Positive and insignificant results between the principal's transformational leadership style to teacher innovation. The result of the research which shows negative and not significant is teacher's motivation to teacher performance. While the results of teacher innovation testing to teacher performance showed a negative and significant influence. These results it can be concluded that the principal's transformational leadership style does not require intervening motivation and innovation of teacher variables to influence teacher performance..